Analisis Pemesanan Hosting PT Qwords Company International Menggunakan Metode K-Means Clustering - Cahyo Prianto; Shinta Amelia (SMATIKA JURNAL, 2019)
Qwords.com is a web hosting service company that serves domain name registration and web hosting. Qwords.com was established on July 10, 2005, and started using the Qwords.com brand since August 28, 2005. Hosting is a place to create web pages that have been made onlide, so that others can access them. In this study, the outhor found a problem, namely the difficulty of finding clients who often host in the area and from the company where the clients from. So the company is difficult to determine the target of promotion that will be done. Therefore, we need a method that can solve problems that exist to provide output in the form of calculation results that show the most purchased products in the category of hosting packages in 2017, and later this data is useful to determine the target of promotion.